Necesidad de reformar el art.75 del código orgánico integral penal, en cuanto a la imprescriptibilidad de los delitos contra la vida - Loayza Aguilar, María Elizabeth (2014)
The article 66 of the Constitution of the Republic of the Ecuador, provides in its paragraph 1 that guarantees "the right to the inviolability of life. There will be no death penalty". It is said that this body of law guarantees the right and the freedom to enjoy a dignified life, respecting the rights of society in general, is forbidden to the sanctity of this right. That is why today, are aggravating the high levels of crime, where death is given to the victim, the absence of a means to make the penalty that punishes this crime imprescriptible, since there are cases where criminals waiting time for the prescription of the penalty, as failure to comply with the justice. It is noteworthy that the comprehensive criminal code in its article 75 last subparagraph determined only that "they do not prescribe the penalties specified in the offences of genocide, aggression, war crimes, forced disappearance of persons, crimes of aggression to a State, embezzlement, bribery, concussion, illicit enrichment, and environmental damage, against humanity" Requiring a legal reform to this last body of law, the right to life is a constitutional guarantee, and the attack against this, is more serious and social alarm that offences against the public administration.